Perancangan Game Kasual Pongo Tap Pixel Art 2D - Bayu Robyananta Saputra; Rinawati Ciptaningrum (Syntax Idea)
Interactive multimedia applications play a very important role as a medium for information, socialization and education. Video games as part of interactive digital applications have the opportunity to be an effective entertainment and learning medium, if designed appropriately. The casual game PongoTap can be used as a socialization medium to increase public awareness of the importance of preserving orangutan habitat. Information about orangutans in 2017, orangutans are included in the Red List of critically endangered (CR) animals whose population is estimated to continue to decline. Based on these reasons, the game concept tells the story of a young orangutan who has lost his habitat, and must go on an adventure to try to survive by finding a comfortable place for him. Pongo is the main character in this casual game. The methodology in game design uses research and development (Research & & Development). Data collection was carried out by searching for library data (supporting theories) and factual data (creation sources) and then data processing was used as a reference in preparing the game design concept. The visual appearance of Pongo Tap 2D is in pixel art style. The game is designed in 4 stages, each stage is identical with a different level regarding; gameplay, characters, and environment. The final result of the creation stage is an interactive application in the form of a video game for Android-based smartphone devices. Conclusion of design analysis; side scrolling platformer gameplay, orangutan characters, and endemic animal habitat environments.